Integrating Islamic values in CLIL materials: a syllabus design for Islamic primary school - Khoiriyah Khoiriyah; Rafika Rabba Farah; Luciana Anggraeni (English Department - University of Sultan Ageng Tirtayasa, 2022)
The new educational policy in Indonesia does not require English as a compulsory subject in primary school. To respond to the current policy, some primary schools, especially Islamic affiliated primary schools still have a commitment to provide English lessons as an extracurricular subject. Since there is no regulation toward the teaching and learning process, implementing Content-Language Integrated Learning (CLIL) approach into teaching materials aims to improve the learning process. This study used ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model to design the CLIL materials and reached the third stage. The results highlight that after conducting a need analysis, the syllabus and the students’ activity book consists of three selected topics that integrate Islamic values into CLIL model. They were Caring for Living Things, My Heroes, and My Dream Job. Those topics were adapted from a thematic book applied in the school partner under the Curriculum 2013. These topics were designed into three main subjects i.e., Science, Islamic Content, and Arts. Furthermore, before each topic, vocabulary-based activities were presented followed by three kinds of activities. Islamic values are integrated into CLIL materials to promote Contextual Teaching and Learning (CTL) also to advocate local wisdom-based curriculum, particularly infusing the Muslim cultures and values. This study concludes that there is a need to integrate Islamic content to English materials in Islamic primary affiliated schools.